2018
DOI: 10.1073/pnas.1809662115
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 pore turret dictates distinct DkTx and capsaicin gating

Abstract: Many neurotoxins inflict pain by targeting receptors expressed on nociceptors, such as the polymodal cationic channel TRPV1. The tarantula double-knot toxin (DkTx) is a peptide with an atypical bivalent structure, providing it with the unique capability to lock TRPV1 in its open state and evoke an irreversible channel activation. Here, we describe a distinct gating mechanism of DkTx-evoked TRPV1 activation. Interestingly, DkTx evokes significantly smaller TRPV1 macroscopic currents than capsaicin, with a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 64 publications
(133 reference statements)
7
46
0
Order By: Relevance
“…The value is slightly lower than that estimated from current recordings, an observation resembling that for capsaicin (Figure S1). Similar observations were previously reported and attributed to differences in the two detection methods (Geron et al, ). Importantly, the T551V mutation shifted the concentration–response curve substantially to the right, increasing the EC 50 value to 3.9 ± 0.5 μM ( n = 6).…”
Section: Resultssupporting
confidence: 91%
“…The value is slightly lower than that estimated from current recordings, an observation resembling that for capsaicin (Figure S1). Similar observations were previously reported and attributed to differences in the two detection methods (Geron et al, ). Importantly, the T551V mutation shifted the concentration–response curve substantially to the right, increasing the EC 50 value to 3.9 ± 0.5 μM ( n = 6).…”
Section: Resultssupporting
confidence: 91%
“…As for changes in the conductance of TRPV1 due to the actions of agonists, it is interesting to note that, it has been recently reported that DkTx diminishes the unitary conductance by 32% of TRPV1, as compared to that observed with capsaicin [159]. DkTx is a molecule composed of two moieties joined by a short linker, which bind in the outer pore region of the channel so that each motif sits at a subunit interface [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a TRPV2 channel engineered to be sensitive to RTX, an even more drastic dilation of the upper gate was recently observed as the channel transitions from fourfold to twofold symmetry upon binding RTX (Zubcevic et al, 2018b), further confirming the existence of an upper gate within the TRPV channels. Such flexibility within the TRPV1 outer pore region also likely contributes to distinct single-channel conductance states evoked by different TRPV1 agonists (Canul-Sánchez et al, 2018; Geron et al, 2018).…”
Section: The “Resolution Revolution” Led To Breakthrough In Trpv1 Structural Biologymentioning
confidence: 99%